ANALISIS KEMAMPUAN MEMBACA CEPAT DAN PEMAHAMAN SISWA KELAS IV SD NEGERI MELAYU 2 BANJARMASIN - Maryanti, Nova Nur; Agustina, Lili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Rapid reading ability and comprehension are essential in learning activities to acquire information. However, students frequently face obstacles that lead to low rapid reading skills, such as a lack of self-confidence, bad habits, and concentration disruptions. This study aims to analyze rapid reading ability and comprehension while identifying the inhibiting factors among fourth-grade students at SD Negeri Melayu 2 Banjarmasin. This study employed a descriptive mixed-methods approach combining quantitative and qualitative methods. The research subjects consisted of a teacher and 17 fourth-grade students. Data were collected through reading tests, interviews, and observations, then analyzed through data reduction, data display, and data verification, with data validity tested through source and technique triangulation. The results showed that the students' rapid reading ability and comprehension were divided into three categories: moderate with 7 students (41.18%), low with 7 students (41.17%), and fast with 3 students (17.65%). Based on the indicators of factors inhibiting rapid reading comprehension, the results indicated that students scored: pointing with fingers at 63% (fair), regression at 64% (fair), head movement at 66% (fair), lip movement at 69% (fair), vocalization at 72% (good), and subvocalization at 89% (very good). These findings indicate that effective reading practice is still required to enhance students' reading speed and comprehension.